Analisis Sosial Media Pemerintah Daerah Di Indonesia Berdasarkan Respons Warganet - Widiasih, Suprapti; Julina, Faizah; Salsabila, Indah Septiani (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
The use of electronic Government (e-Government) in the form of social media by local governments is used to increase interaction between the government and the community. But in reality, this e-Government service in the form of social media has still not received a response from the public. Thus, a strategy of posting variations used in the form of videos, images, or text is needed to obtain responses from the public in the form of likes on social media. The purpose of this study is to analyze the 39 most active local government social media based on likes and analysis of public sentiment. The data collection method with crawling techniques uses the Facebook API. The data is divided into three categories, including images, videos, and text. The findings obtained from this study are that posts in the form of videos on social media get more positive responses than posts in the form of images and text. In addition, based on public sentimental analysis, the level of sentiment on the Facebook page of local governments in Indonesia is relatively positive.